Implementation of Public Service Digitalization at The Tawiri Village Office Teluk Ambon Districk Ambon - Kastanya, Siska Lorensa; Ubjaan, Jusak; F.G.Renyut, Selvia (Pinisi Business Administration Review, 2025)
This research aims to analyze the implementation of public service digitalization at the Tawiri Village Office, TelukAmbon District. In the era of technological advancement, digitalization has become one of the solutions to improve the efficiency and quality of public services. This study employs a descriptive method with a qualitative approach to illustrate how information technology is implemented in village administrative services, such as letter issuance, population data management, and communication between residents and village officials.. The findings reveal that the implementation of digitalization has provided convenience for the community in accessing services, accelerated administrative processes, and reduced the risk of data errors. However, challenges remain, such as the limited number of human resources skilled in technology and the uneven distribution of internet infrastructure, which hinder the optimal digitalization process in Tawiri Village. This study recommends further training for village officials and improvements in access to and quality of technological infrastructure to support the smooth implementation of digitalizationKeywords:  Digitalization; Public Serice; Tawiri Village